Controlling parameters for jatropha biodiesel production in a batch reactor - Kabbashi, Nassereldeen Ahmed; Mohammed, Nurudeen Ishola; Alam, Md. Zahangir; Mirghani, Mohammed Elwathig S. (IEEE, 2015)
In a quest for environmental friendly energy source with least pollutants emission due to issues of global warming coupled with dwindling reserve of the fossil fuel which has been the energy source for ages, researchers have intensified study on renewable fuels among which biodiesel stands prominent. Biodiesel production is largely by transesterification of transglycerides of fatty acids almost always in a batch reactor. Of importance in the yield generation and FAME conversion achievement is the control of reagents use in production and operation parameters control. This will afford optimum resource conservation while also minimize cost and materials wastage. In this study biodiesel was produced from hydrolysate (FFA) of Jatropha curcas oil using calcinated niobic acid catalyst at controlled rates of process parameters. Yield and conversion of the alkyl esters produced inform the influence of control parameters significantly on the throughput of the final product.